KEMAMPUAN MENULIS PUISI PESERTA DIDIK KELAS IV SDN 27 WOJA TAHUN PELAJARAN 2020/2021 - Aprilia Pratiwi; Siti Rohana Hariana Intiana; Syafruddin Syafruddin; I Ketut Widiada (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2022)
This study aims to determine the poetry writing skills of fourth grade students of SD Negeri 27 Woja. The problems studied in this study are the elements of poetry which include themes, mandate, diction, imagination, and explanation. This type of research used in this research is qualitative research with descriptive methods. The data collection technique used is documentation technique. The technique of presenting the results of data analysis used is an informal method. Based on the results of data analysis, it can be concluded that (1) the ability of grade IV SDN 27 Woja students in writing poetry in terms of theme elements is in the Good category. This is because the average score obtained is 79.2 (good category), (2) The ability of grade IV SDN 27 Woja students in writing poetry in terms of mandate is in the Enough category. This is because the average value is 74.45 (sufficient category), (3) The ability of grade IV SDN 27 Woja students in writing poetry in terms of diction elements is in the sufficient category, this is because the average score of students is 69.25 (Enough category), (4) The ability of grade IV SDN 27 Woja students in writing poetry in terms of the element of imagination is in the sufficient category, this is because the average score of students is 67.9 (Enough category), (5) The ability of grade IV SDN 27 Woja in writing poetry in terms of the elements of exposure is in the sufficient category, this is because the average score of students is 64.9 (Enough category). The average score obtained by students for all elements, namely 71.14, is in the (Enough category).